The Impact of Adult Deaths on Children's Health in Northwestern Tanzania - Ainsworth, Martha; Semali, Innocent (World Bank, Washington, DC, 2015)
The AIDS epidemic is dramatically increasing mortality of adults in many Sub-Saharan African countries, with potentially severe consequences for surviving family members. Until now, most of these impacts had not been quantified. The authors examine the impact of adult mortality in Tanzania on three measures of health among children under five: morbidity, height for age, and weight for height. The children hit hardest by the death of a parent or other adult are those in the poorest households, those with uneducated parents, and those with the least access to health care. The authors also show how much three important health interventions--immunization against measles, and rehydration salts, and access to health care--can do to mitigate the impact of adult mortality. These programs disproportionately improve health outcomes among the poorest children and, within that group, among children affected by adult mortality. In Tanzania there is so much poverty, and child health indicators are so low that these interventions should be targeted as much as possible to the poorest households, where the children hit hardest by adult mortality are most likely to be found. (Conceivably, the targeting strategy for middle-income countries with severe AIDS epidemics, such as Thailand, or countries with less poverty and better child health indicators might be different.)